Histone methyltransferase G9a is a key regulator of the starvation-induced behaviors in Drosophila melanogaster. Issue 1 (December 2017) - Shimaji, Kouhei; Tanaka, Ryo; Maeda, Toru; Ozaki, Mamiko; Yoshida, Hideki; Ohkawa, Yasuyuki; Sato, Tetsuya; Suyama, Mikita; Yamaguchi, Masamitsu
Abstract Organisms have developed behavioral strategies to defend themselves from starvation stress. Despite of their importance in nature, the underlying mechanisms have been poorly understood. Here, we show thatDrosophila G9a (dG9a), one of the histone H3 Lys 9-specific histone methyltransferases, functions as a key regulator for the starvation-induced behaviors. RNA-sequencing analyses utilizingdG9a null mutant flies revealed that the expression of some genes relating to gustatory perception are regulated by dG9a under starvation conditions. Reverse transcription quantitative-PCR analyses showed that the expression of gustatory receptor genes for sensing sugar are up-regulated in starveddG9a null mutant. Consistent with this, proboscis extension reflex tests indicated thatdG9a depletion increased the sensitivity to sucrose under starvation conditions. Furthermore, the locomotion activity was promoted in starveddG9a null mutant. We also found thatdG9a depletion down-regulates the expression ofinsulin-like peptide genes that are required for the suppression of starvation-induced hyperactivity. Furthermore, refeeding of wild type flies after starvation conditions restores the hyperactivity and increased sensitivity to sucrose as well asdG9a expression level. These data suggest that dG9a functions as a key regulator for the decision of behavioral strategies under starvation conditions.